Role of cis-12-Oxo-Phytodienoic Acid in Tomato Embryo Development(1)([C])([W]) - Goetz, Stephan (American Society of Plant Biologists, 2012)
Oxylipins including jasmonates are signaling compounds in plant growth, development, and responses to biotic and abiotic stresses. In Arabidopsis (Arabidopsis thaliana) most mutants affected in jasmonic acid (JA) biosynthesis and signaling are male sterile, whereas the JA-insensitive tomato (Solanum lycopersicum) mutant jai1 is female sterile. The diminished seed formation in jai1 together with the ovule-specific accumulation of the JA biosynthesis enzyme allene oxide cyclase (AOC), which correlates with elevated levels of JAs, suggest a role of oxylipins in tomato flower/seed development. Here, we show that 35S::SlAOC-RNAi lines with strongly reduced AOC in ovules exhibited reduced seed set similarly to the jai1 plants. Investigation of embryo development of wild-type tomato plants showed preferential occurrence of AOC promoter activity and AOC protein accumulation in the developing seed coat and the embryo, whereas 12-oxo-phytodienoic acid (OPDA) was the dominant oxylipin occurring nearly exclusively in the seed coat tissues. The OPDA- and JA-deficient mutant spr2 was delayed in embryo development and showed an increased programmed cell death in the developing seed coat and endosperm. In contrast, the mutant acx1a, which accumulates preferentially OPDA and residual amount of JA, developed embryos similar to the wild type, suggesting a role of OPDA in embryo development. Activity of the residual amount of JA in the acx1a mutant is highly improbable since the known reproductive phenotype of the JA-insensitive mutant jai1 could be rescued by wound-induced formation of OPDA. These data suggest a role of OPDA or an OPDA-related compound for proper embryo development possibly by regulating carbohydrate supply and detoxification.